CT-based MCNPX dose calculations for gynecology brachytherapy employing a Henschke applicator. (November 2017) - Yu, Pei-Chieh; Nien, Hsin-Hua; Tung, Chuan-Jong; Lee, Hsing-Yi; Lee, Chung-Chi; Wu, Ching-Jung; Chao, Tsi-Chian
Abstract: The purpose of this study is to investigate the dose perturbation caused by the metal ovoid structures of a Henschke applicator using Monte Carlo simulation in a realistic phantom. The Henschke applicator has been widely used for gynecologic patients treated by brachytherapy in Taiwan. However, the commercial brachytherapy planning system (BPS) did not properly evaluate the dose perturbation caused by its metal ovoid structures. In this study, Monte Carlo N-Particle Transport Code eXtended (MCNPX) was used to evaluate the brachytherapy dose distribution of a Henschke applicator embedded in a Plastic water phantom and a heterogeneous patient computed tomography (CT) phantom. The dose comparison between the MC simulations and film measurements for a Plastic water phantom with Henschke applicator were in good agreement. However, MC dose with the Henschke applicator showed significant deviation (−80.6%±7.5%) from those without Henschke applicator. Furthermore, the dose discrepancy in the heterogeneous patient CT phantom and Plastic water phantom CT geometries with Henschke applicator showed 0 to −26.7% dose discrepancy (−8.9%±13.8%). This study demonstrates that the metal ovoid structures of Henschke applicator cannot be disregard in brachytherapy dose calculation. Highlights: MCNPX dose simulation in patient CTs with Henschke applicator. MC and film agree well in a Plastic water phantom with Henschke applicator. Significant dose deviation caused by metal ovoids of the Henschke applicator.